Spillage and displacement of indocyanine green-stained tissues from uterine cervix to pelvic peritoneum: A proof of concept study for colpotomy approach in minimally invasive surgery - Tae-Wook Kong; Jimin Lee; Sun Hyung Yum; Jeeyeon Kim; Joo-Hyuk Son; Suk-Joon Chang; Hee-Sug Ryu (Elsevier, 2023)
Objective: To analyze peritoneal spillage and displacement of indocyanine green (ICG)-stained tissues from uterine cervix to pelvis during intracorporeal/vaginal colpotomy in laparoscopic-assisted hysterectomy. Materials and methods: Eleven patients undergoing laparoscopic-assisted hysterectomy were included. One patient with an incidental diagnosis of endometrial cancer was excluded. Of the 10 patients, five underwent intracorporeal colpotomy (IC) and five received vaginal colpotomy (VC) during laparoscopic-assisted hysterectomy. Approximately 5 cm of resected round ligament from each patient was stained with ICG and cut to 1.0 × 1.0 cm in size. Four to five fragments of ICG-stained tissues were placed and sutured on the uterine cervix before colpotomy. During and after colpotomy, serial pictures under white and fluorescence light were taken to document peritoneal spillage and displacement of ICG-stained tissues to the pelvic peritoneum. Results: Peritoneal spillage of ICG occurred in the entire IC group. Displacement of ICG-stained tissues from uterine cervix to pelvic peritoneum were visualized in three (60%) patients undergoing IC. In the five patients who received VC, peritoneal spillage of ICG and displacement of ICG-stained tissue to pelvic peritoneum did not occur. There were no perioperative complications. Conclusions: IC in minimally invasive radical hysterectomy should not be performed because peritoneal spillage of ICG and displacement of ICG-stained tissues from uterine cervix to pelvis frequently occurs during IC. Therefore, specific measures to prevent tumor exposure during colpotomy should be implemented in cervical cancer patients.